Toward a Theory of Peace : The Role of Moral Beliefs - Forsberg, Randall (Book collections on Project MUSE., 2019)
"This book explores the conditions under which the institution of war could be brought to an end. It draws on an extensive program of research into the phenomenon of socially sanctioned violence and focuses on the role of moral beliefs. This book explores social change and the goal of eradicating mass violence"--